Austria : 2009 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Austria. (IMF Staff Country Reports; Country Report, 2009)
This report is focused on the impact of the financial crisis on the Austrian economy and the financial sector, the authorities' policy responses, and macrofinancial linkages and spillovers. The financial sector has been expanding rapidly, mostly outside Austria. This has brought substantial benefits, but also increased risks and vulnerabilities. Maintaining financial stability will be essential for ensuring macroeconomic stability, fiscal sustainability, and a return to growth, while also having important spillovers to regional financial stability. Austria traditionally benefits from a low unemployment rate compared with the euro area.